Rationality : What it is, Why it Seems Scarce, Why it Matters - Pinker, Steven (UK Penguin Books, 2022)
"Can reading a book make you more rational? Can it explain why there seems to be so much irrationality in the world, including, let's be honest, in each of us? These are the goals of Steven Pinker's follow-up to Enlightenment Now (Bill Gates's "new favourite book of all time"). Humans today are often portrayed as cavemen out of time, poised to react to a lion in the grass with a suite of biases, blind spots, fallacies, and illusions. But this, Pinker a cognitive scientist and rational optimist argues, cannot be the whole picture. Hunter-gatherers--our ancestors and contemporaries--are not nervous rabbits but cerebral problem-solvers. A list of the ways in which we are stupid cannot explain how we're so smart: how we discovered the laws of nature, transformed the planet, and lengthened and enriched our lives. Indeed, if humans were fundamentally irrational, how did they discover the benchmarks for rationality against which humans fall short? The topic could not be more timely. In the 21st century, humanity is reaching new heights of scientific understanding--and at the same time appears to be losing its mind. How can a species that sequenced the genome and detected the Big Bang produce so much fake news, quack cures, conspiracy theories, and "post-truth" rhetoric? A big part of Rationality is to explain these tools--to inspire an intuitive understanding of the benchmarks of rationality, so you can understand the basics of logic, critical thinking, probability, correlation and causation, the optimal ways to adjust our beliefs and commit to decisions with uncertain evidence, and the yardsticks for making rational choices alone and with others. Rationality matters. As the world reels from foolish choices made in the past and dreads a future that may be shaped by senseless choices in the present, rationality may be the most important asset that citizens and influencers command. Steven Pinker, the great defender of human progress, having documented how the world is not falling apart, now shows how we can enhance rationality in our lives and in the public sphere. Rationality is the perfect toolkit to seize our own fates"--
Include Illustrations, References and Index
Keywords: Practical reason -- Choice (Psychology) -- Critical thinking